2011
DOI: 10.1007/s10592-011-0244-7
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity, population genetic structure and demographic history of Przewalski’s gazelle (Procapra przewalskii): implications for conservation

Abstract: The Przewalski's gazelle (Procapra przewalskii) is one of the most endangered antelope species in the world. It is endemic to China and is a flagship species in the eastern part of the Qinghai-Tibet plateau. To establish effective conservation measures on this species, genetic information such as genetic structure is needed. However, there has not been a comprehensive genetic assessment on this gazelle using nuclear DNA markers yet. Here, we employed 13 microsatellite loci to investigate genetic diversity, pop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 41 publications
2
19
0
1
Order By: Relevance
“…Yang et al also got similar results ( H O = 0.525 and H E = 0.552) in the study of genotyping and analyzing 169 individuals from nine subpopulations of P. przewalskii [39]. Possible reasons are that P. przewalskii has recently experienced a severe population decline and a genetic bottleneck [26,39,43]. Our result highlights the conservation emergency of the endangered P. przewalskii again.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Yang et al also got similar results ( H O = 0.525 and H E = 0.552) in the study of genotyping and analyzing 169 individuals from nine subpopulations of P. przewalskii [39]. Possible reasons are that P. przewalskii has recently experienced a severe population decline and a genetic bottleneck [26,39,43]. Our result highlights the conservation emergency of the endangered P. przewalskii again.…”
Section: Resultssupporting
confidence: 79%
“…However, the number of alleles ( N = 4.75), observed heterozygosity ( H O = 0.593) and expected heterozygosity ( H E = 0.654) of P. przewalskii were all significantly lower than for both P. picticaudata , and P. gutturosa , manifesting lower genetic diversity in the endangered gazelle. Yang et al also got similar results ( H O = 0.525 and H E = 0.552) in the study of genotyping and analyzing 169 individuals from nine subpopulations of P. przewalskii [39]. Possible reasons are that P. przewalskii has recently experienced a severe population decline and a genetic bottleneck [26,39,43].…”
Section: Resultsmentioning
confidence: 71%
“…We never found individuals that moved from Hudong-Ketu to Yuanzhe area during our field tracking surveys and our results show that habitat area of the local populations were clearly reduced after the grassland was fenced in the early 1990s (Figure 3). Recent reports on the genetic structure of the Przewalski's gazelle also indicated the anthropogenic landscape had deeper impacts on the population structure than lake and mountains [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…The habitat of the Ganzihe population is a mosaic of steppe, desert and wetland, while the Hargai population lives in a vast area of steppe less than 40 km away from Ganzihe. In this study, they are combined into a single Hargai population (the Gahai population of Lei et al [27]), as there are no robust geographical barriers between the two, and the genetic evidence shows that there are still a few individual exchanges between the populations [18].…”
Section: Study Areamentioning
confidence: 99%
“…Recent surveys found that the Tibetan and Przewalski's gazelle still live in the steppe ecosystem in a valley of the Upper Buha River [1]. Although the two species do share morphological similarities, there are distinct differences in the shape of the horns as well as the structure of the skull; molecular data [17,18] suggest that P. przewalskii may in fact be more closely related to the Mongolian gazelle, P. gutturosa, than to P. picticaudata. Recent molecular evidences supported the hypothesis.…”
mentioning
confidence: 99%